Analisis Kebutuhan Wirausaha Bagi Pemuda Buddhis Di Vihara Sekecamatan Cikarang Kabupaten Bekasi - Parjono Parjono (STABN Sriwjaya, 2020)
The research background is based on the entrepreneur needs of Monastery young man in Cikarang sub-district, Bekasi district. The purpose of this study was to determine the views of the monastery youth on the needs of entrepreneurship, the required fields of entrepreneurship, techniques for developing entrepreneur skills and the conditions expected by monastery youth regarding entrepreneur needs. The method used in this research is descriptive qualitative research. The research subject was the Monastery young man in Cikarang sub-district, Bekasi district, the object of research was entrepreneur needs. The research location is at the Monastery which is located in the Cikarang sub-district, Bekasi district. Data collection techniques and instruments through observation, interviews and documentation. Based on the findings in the field, the results obtained are: 1) entrepreneur among Monastery young man in Cikarang sub-district, Bekasi district is very much needed because it aims to help the family economy, earn income, continue parents' businesses, gain experience and train independence and as a solution to the difficulty of getting a job; 2) the fields of entrepreneurship needed by the Monastery young man are trading in the sectors of basic necessities, culinary, electrical, electronic, pet shops and animal care services; 3) Techniques to develop entrepreneur skills for young people are to become entrepreneurs directly, learn via the internet, and be self-taught by actively helping run parents' businesses; 4) the conditions expected by Monastery young mans regarding entrepreneur needs are to expect an active role of Monastery young man organizations in planning and implementing entrepreneur skills coaching and training activities, support from Monastery and Foundation administrators, capital assistance